Building National Identity from Within: The Role of Self-Competence in Strengthening National Identity - B. Baydhowi; M. Preston; V. Syahputra; A.D. Cahyani; D. Rabitha (Социальная психология и общество)
Objective. This study examines how an individual's self-competence is related to their national identity. Additionally, the study investigates how the self-concept of own competence mediates in that relationship. Background. People with a high internal locus of control frequently think that hard work and wise choices can produce favorable results. Self-competence can be favorably impacted by decision-making skills and self-assurance in one's ability to make personal decisions. People see themselves as special individuals with the capacity to achieve goals and overcome challenges in a variety of spheres of life. Having a positive self-image of one's own competence can have a significant effect on a person's life, including their feeling of national identity. Self-perception of one's own skill and aptitude can enable people to make positive contributions to the prosperity and advancement of their country. The self-concept of one's own competence serves as a bridge between locus of control and national identity. People who believe they are competent and capable are more inclined to participate in national identity-building activities. Study Design. The research adopts a quantitative approach using Structural Equation Modeling (SEM) to test a theoretical mediation model. The study investigates whether self-concept of competence mediates the relationship between internal locus of control and national identity. Participants. The study sample consists of 504 university students (176 men and 328 women), aged between 18 to 25 years, recruited from 20 public and private universities in Jakarta, Indonesia. Measurements. Internal locus of control and self-concept of competence were assessed using the general control beliefs scale, while national identity was measured with the National Identity Scale. Data were analyzed using SEM to assess the proposed relationships between these variables. Results. The results revealed a significant relationship between internal locus of control and national identity, with self-concept of competence acting as a partial mediator. The findings indicate that individuals with higher internal locus of control tend to perceive themselves as competent and are more likely to strongly identify with their nation. Model fit indices demonstrated good fit (Chi-square = 0,077, CFI = 1,00, RMSEA = 0,024, SRMR = 0,026). Conclusions. The study highlights the importance of internal locus of control and self-concept of competence in the development of national identity. Interventions aiming to foster national cohesion and engagement can benefit from focusing on enhancing individuals' self-perception of competence and empowering them to take active roles in their communities. These findings provide practical implications for psychological and educational strategies to strengthen national identity formation.